Can CBT-E be delivered in an online group format? A pilot study of the Body Image module in a child and adolescent eating disorder service. Issue 3 (4th May 2023) - Hamadi, Layla; Hilson, Reece; Lunn, Amy; Ralph, Emily; Rodrigues, Evangeline; Sohail, Rabeeah
ABSTRACT: The increased prevalence of eating disorders during the COVID-19 pandemic has led to long waiting lists in child and adolescent services. A pilot study was conducted to evaluate the feasibility and acceptability of providing the Body Image module, from the enhanced cognitive behavioral therapy for eating disorders (CBT-E), in a virtual group setting. Primary outcomes were acceptance rates, completion rates, qualitative feedback and quantitative data from routine questionnaires. From 22 eligible referrals, 12 participants accepted and enrolled in therapy. Eight completed all six sessions. Qualitative feedback was positive, with both the content and group nature of the intervention being described as helpful. There was an reduction in scores in the Clinical Impairment Assessment and all subscales of the Eating Disorder Examination for Adolescents, suggesting this was a feasible method of providing psychological therapy within the service. A larger trial is recommended to robustly test the effectiveness of the intervention compared to one-to-one in-person CBT-E, and whether the full CBT-E protocol can be effectively delivered in the same format.